O źródłach motywacji w kontekście edukacji językowej dorosłych - Róg, Tomasz (Neofilolog, 2019)
This paper concerns the teaching of foreign languages to adults with special attention given to the concept of motivation. The present author wishes to present the findings of his small-scale research done on a group of adults and their teachers as regards the sources of motivation in the context of adult language instruction. To begin with, an overview of the notion of mo-tivation is followed by its typology and current state of knowledge about teaching languages to adults is briefly outlined. The second part of the arti-cle demonstrates the procedure and results of the study.